Pembuatan Deodoran Spray Alami Berbasis Daun Sirih Hijau (Piper Betle L.) - Nuriennabila, Nuriennabila; Sari, Ratna; Satriananda, Satriananda (Politeknik Negeri Lhokseumawe, 2025)
Problems of cleanliness and body odor often reduce a person's self-confidence. The use of natural spray deodorants based on green betel leaves (Piper betle L.) was developed as a safer alternative to synthetic deodorants. This study aims to determine the effect of variations in the concentration of propylene glycol and betel leaf extract on the physical properties of spray deodorants, such as specific gravity, viscosity, pH, and skin irritation, and to evaluate the safety of the product in daily use. Betel leaves were extracted using the maceration method with 96% ethanol solvent, and the spray deodorant formulation was made with variations in the concentration of propylene glycol of 3%, 4%, 5%, 6%, and 15%, and betel leaf extract of 0.1%, 0.2%, 0.3%, 0.4%, and 0.5%. The results showed that the formulation with a 5% propylene glycol concentration gave the best results, in accordance with SNI standards for specific gravity (1.0185), viscosity (0.516 cP), and pH (4.5), which are within the standard pH range of 4.4-7 for cosmetic products. In addition, the concentration of betel leaf extract of 0.5% produced the highest organoleptic test value with a score between 3.7 and 4.7, indicating that this product is safe to use without causing significant skin irritation.